الدراسة التجريبية لتأثير شكل الصفيحة الماصة على الأداء الحراري للاقط الشمسي الهوائي - رامي جورج; ماهر زوزو (Tishreen University, 2018)
The objective of the research is to improve the thermal performance of the solar air collector. By providing it by absorber plate with different dimensions and shapes. To determine the optimal shape of absorber, in order to achieve high efficiency comparing with conventional solar air collector with flat absorber plate. The experiments were carried out for both collector under the same metrological conditions of Lattakia city. This investigation showed that the outlet air temperature from collector with corrugated absorber plate is higher than that for flat ad waved plate. This investigation showed that the thermal performance of solar air collector with corrugated absorber plate (V shape) is biter than case of flat plate absorber. The maximum thermal performance values are 41.5[%] ad 30[%] respectively. Where the maximum difference is 14.36 [%] in 3/1/2017. Also this investigation showed that the thermal performance of solar air collector with corrugated absorber plate placed perpendicular to air flow is higher than parallel location. The maximum thermal performance values are 32[%] and 26[%] respectively. Where the maximum difference is 10 [%] in 16/1/2017.   يهدف البحث إلى تحسين الأداء الحراري للاقط الشمسي الهوائي تجريبياً من خلال تزويده بصفيحة ماصة ذات أبعاد وأشكال مختلفة. لتحديد الشكل الأمثل بما يحقق مردوداً حرارياً أعلى للاقط مقارنة مع اللاقط الشمسي التقليدي ذو الصفيحة الماصة المستوية. أجريت التجارب لكلا اللاقطين عند نفس الشروط المناخية لمدينة اللاذقية. أظهرت نتائج البحث التجريبية أن درجة حرارة الهواء الخارج من اللاقط الشمسي المزود بصفيحة ماصة منكسرة أعلى منها في حالة اللاقط ذو الصفيحة المستوية أو المتموجة. وكلما كانت موجة الصفيحة المنكسرة أكبر، حصلنا على درجة حرارة أعلى للهواء. أظهرت نتائج البحث التجريبية أيضاً أن الأداء الحراري للاقط الشمسي الهوائي المزود بصفيحة ماصة منكسرة على شكل حرف V  هو الأفضل مقارنة مع اللاقط ذو الصفيحة الماصة المستوية. حيث بلغت القيمة العظمى للمردود الحراري اللحظي للاقط  41.5[%]بينما بلغت قيمته العظمى للاقط ذو الصفيحة الماصة المستوية ]%30[. وبلغت أكبر زيادة في المردود 14.36 [%] وذلك في يوم 3/1/2107. كما أظهرت نتائج البحث التجريبية أن مردود اللاقط الشمسي الهوائي ذو الصفيحة الماصة المنكسرة بموجات متعامدة مع اتجاه دخول الهواء أعلى منه في حالة الموجات الموازية لاتجاه دخول الهواء. وقد بلغت أعلى قيمة للمردود اللحظي 32[%] و  26[%]على التوالي. بينما بلغت أكبر زيادة في المردود 10[%] وذلك في يوم 16/1/2017.